ANALISIS PENGELOLAAN DANA DESA BERDASARKAN PERMENDAGRI NOMOR 113 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN DESA (STUDI KASUS DESA PURWAJAYA KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA) - Andi Indrawati, Abi Oktaviannur, Mardiana, (EKONOMIA, 2020)
The aim of which is the know is to find out the suitability of Purwajaya Village financial management based on the Permendagri number 113 year 2014 government regulation on village financial management. Data collection techniques that are done namely, field research, observasion, interview, quiestionnnaire, and library research. The population and sample size of the study were nine people consisting of village officials by distributing questionnaires. The analytical tool used is questionnaire. The results of the analysis put forward it can be seen that the financial management of Purwajaya Village is in accordance with the Permendagri regulation number 113 of 2014 concerning village financial management, which is reviewed from five aspect, namely planing, implementation, administration, reporting, responsibility.